Chemical Design of Non‐Ionic Polymer Brushes as Biointerfaces: Poly(2‐oxazine)s Outperform Both Poly(2‐oxazoline)s and PEG. Issue 36 (13th August 2018) - Morgese, Giulia; Verbraeken, Bart; Ramakrishna, Shivaprakash N.; Gombert, Yvonne; Cavalli, Emma; Rosenboom, Jan‐Georg; Zenobi‐Wong, Marcy; Spencer, Nicholas D.; Hoogenboom, Richard; Benetti, Edmondo M.
Abstract: The era of poly(ethylene glycol) (PEG) brushes as a universal panacea for preventing non‐specific protein adsorption and providing lubrication to surfaces is coming to an end. In the functionalization of medical devices and implants, in addition to preventing non‐specific protein adsorption and cell adhesion, polymer‐brush formulations are often required to generate highly lubricious films. Poly(2‐alkyl‐2‐oxazoline) (PAOXA) brushes meet these requirements, and depending on their side‐group composition, they can form films that match, and in some cases surpass, the bioinert and lubricious properties of PEG analogues. Poly(2‐methyl‐2‐oxazine) (PMOZI) provides an additional enhancement of brush hydration and main‐chain flexibility, leading to complete bioinertness and a further reduction in friction. These data redefine the combination of structural parameters necessary to design polymer‐brush‐based biointerfaces, identifying a novel, superior polymer formulation. Abstract : By comparing the structural and physicochemical properties of poly(2‐oxazoline) and poly(2‐oxazine) brushes with those of the "gold standard" PEG, a novel superior polymer formulation for the functionalization of biomaterials was identified, redefining the design parameters for polymer‐brush‐based biointerfaces.